The refugee debate in Palestine/Israel: An ongoing narrative of struggles from Palestinians to Africans - Daniele, G. (Border crossings in and out of Europe, 2022)
Since 1948, with the establishment of the state of Israel and the Palestinian Nakba (Catastrophe), the refugee question has become one of the major issues debated not only in historical Palestine, but in many other countries across the world. Throughout its history, the Jewish state has been characterised by successive waves of refugees, each with their own struggles and demands. Accordingly, this chapter aims to analyse the current situation of the most recent waves of non-Jewish African refugees, mainly from Sudan and Eritrea, and their role within the heterogeneous panorama of Israeli social and political activism.